A calibration method for performance analysis in table tennis - Tamaki, S.; Saito, H. (20th Korea-Japan Joint Workshop on Frontiers of Computer Vision, 2015)
A calibration method for performance analysis in table tennis is proposed. Currently, the common method for 3D measurement in sports match scenarios is to compute projection matrix from 3D-2D corresponding points with time-synchronized cameras. There, however, exist several difficulties to conduct it. The proposing method in this paper makes calibration and 3D measurement easier because 3D corresponding points and time-synchronized cameras are not required in this method. It requires only traveling balls in playing area. The key idea of the method is to use 2D ball trajectories to estimate the temporal offset between two cameras by using a traveling ball. It is experimentally demonstrated that the proposing method could calibrate cameras accurately.